Some Thoughts on the Problems of Judicial Elections - Jeffrey Rosinek (My University, 2016)
Reseña:lection season is within sight again, and with it come theElection season is within sight again, and with it come the obligatory attacks on the judiciary. Some call it simply campaigning or electioneering, while others believe it is more serious and a form of “judge bashing.” Whatever name the problems are given, the entire election process may have a marked effect on the independence of our judiciary, as well as the ethics of judges and judicial candidates. And in the end, because these problems affect the public’s faith in the judicial system, they must be addressed...obligatory attacks on the judiciary. Some call it simplycampaigning or electioneering, while others believe it ismore serious and a form of “judge bashing.” Whatever namethe problems are given, the entire election process may have amarked effect on the independence of our judiciary, as well asthe ethics of judges and judicial candidates. And in the end,because these problems affect the public’s faith in the judicialsystem, they must be addressed.